ANALYZING THE IMPACT OF SRI LANKA'S FCY POLICIES ON IMPORT-EXPORT DYNAMICS AND FINANCIAL SECTOR GROWTH - Sivapragasam Sivanenthira; A.R.M. Arshard (PT. Antis International Publisher, 2025)
Objective: This study examines the influence of Sri Lanka's FCY policies on import-export dynamics and financial sector growth amid persistent economic challenges. Method: Utilizing a mixed-methods design, the research integrates macroeconomic data analysis, comprehensive policy review, and stakeholder interviews to assess the ramifications of currency restrictions, exchange rate volatility, and limited FCY availability. Results: The findings reveal that although the current FCY framework contributes to a degree of economic stabilization, significant challenges persist, including notable trade deficits, diminished investor confidence, and operational inefficiencies that impede both trade competitiveness and financial sector expansion. Novelty: By synthesizing quantitative economic evaluations with qualitative insights from key market participants, this study offers novel perspectives on FCY management, presenting actionable policy recommendations designed to mitigate existing constraints and foster sustainable growth in Sri Lanka's trade and financial sectors.